The role of foreign direct investment in the nutrition transition - Hawkes, Corinna (Cambridge University Press, 2005)
To examine the role of foreign direct investment (FDI) in the nutrition transition, focusing on highly processed foods.Data on FDI were identified from reports/databases and then compiled and analysed. A review of published literature on FDI into the food sector was conducted.The nutrition transition is a public health concern owing to its connection with the rising burden of obesity and diet-related chronic diseases in developing countries. Global health leaders are calling for action to address the threat. Highly processed foods often have considerable fat, sugar and salt content, and warrant closer examination.FDI into food processing, service and retail has risen rapidly since the 1980s, mainly from transnational food companies (TFCs) in developed countries. As FDI has risen, so has the proportion invested in highly processed foods for sale in the host market. FDI has proved more effective than trade in generating sales of highly processed foods, and enables TFCs to cut costs, gain market power and obtain efficiencies in distribution and marketing. The amount of FDI targeted at developing countries is increasing; while a disproportionate share enters the larger developing economies, foreign affiliates of TFCs are among the largest companies in low- and low- to middle-income countries. The effect of FDI is to make more highly processed foods available to more people. FDI has made it possible to lower prices, open up new purchasing channels, optimise the effectiveness of marketing and advertising, and increase sales.FDI has been a key mechanism in shaping the global market for highly processed foods. Notwithstanding the role of demand-side factors, it has played a role in the nutrition transition by enabling and promoting the consumption of these foods in developing countries. Empirical data on consumption patterns of highly processed foods in developing countries are critically needed, but since FDI is a long-term investment vehicle, it is reasonable to assume that availability and consumption of highly processed foods will continue to increase. FDI can, however, bring considerable benefits as well as risks. Through its position ‘upstream’, FDI would therefore be an appropriate entry-point to implement a range of public health policies to ‘redirect’ the nutrition transition.